Corporate Governance and Profitability: The Role of Cost of Capital as Mediation - Eka Febiyanti; Hersugondo Hersugondo (University of Merdeka Malang, 2022)
This study aims to analyze the effect of internal corporate governance mechanisms with the cost of capital as mediating variable and profitability as a dependent variable in companies listed on the Indonesia Stock Exchange during period 2015 to 2020. This study uses secondary data collected from Bloomberg's financial data and the company's annual report. A total of 807 companies as a population by sampling with purposive sampling method in order to obtain 300 companies from various sectors. The analysis method employs a structural equation model Structural Equation Modeling (SEM) based on the Partial Least Square (PLS). Based on hypothesis testing through the t-statistical test with a bootstrapping method, the results show that corporate governance has a positive relationship with profitability, and the cost of capital has a fully mediating role in the relationship between corporate governance and profitability.